MHD two-layered unsteady fluid flow and heat transfer through a horizontal channel between parallel plates in a rotating system - Linga Raju, Temburu; Nagavalli, Madhupada (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady magnetohydrodynamic (MHD) two-layered fluids flow and heat transfer in a horizontal channel between two parallel plates in the presence of an applied magnetic and electric field is investigated, when the whole system is rotated about an axis perpendicular to the flow. The flow is driven by a constant uniform pressure gradient in the channel bounded by two parallel insulating plates, when both fluids are considered as electrically conducting, incompressible with variable properties, viz. different viscosities, thermal and electrical conductivities.
Keywords: magnetohydrodynamics; immiscible fluids; rotating fluids; unsteady flow; heat transfer